The Current Situation and Prospect Of Study Quality Evaluation Research in China in The Last 10 Years - Wu Aixia; Zhou Ying; Tommy Tanu Wijaya (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2020)
With the deepening of China's educational reform, the evaluation of teaching quality has become an important aspect of teaching reform.And the evaluation of students'learning quality is an important part of teaching evaluation. Research on it will help to improve the teaching quality of our country and promote the overall improvement of students' morality, intelligence, physical fitness and beauty.Therefore, this study takes 108 literatures related to the study of learning quality evaluation in China as the research object, uses content analysis method, carries out statistical analysis on the annual number of literatures, Journal distribution, author status, paper influence, research content, etc., analyzes the current situation and existing problems of the study of learning quality evaluation in China, and puts forward the need for further deepening.On the basis of these questions, possible future research directions are proposed.